Characterization and Utility of Remote Interpretation of Visual Field Diagnostic Testing in an Academic Center. Issue 1 (17th March 2022) - Kung, Felix F.; Xu, Timothy T.; Leavitt, Jacqueline A.; Lossen, Victoria I.; Lai, Kevin E.; Ko, Melissa W.; Bhatti, M. Tariq; Chen, John J.
Abstract : Background: The use of remote interpretation of data has risen in neuro-ophthalmology to increase efficiency and maintain social distancing due to the coronavirus disease-19 pandemic. The purpose of this study is to characterize the use and efficiency of remote interpretation of visual fields (VFs) in an academic center and to determine how often the VF interpretation was consistent with the patient's clinical history and imaging at the time of the consult. Methods: This is a retrospective study at a single academic center that enrolled all patients receiving a remote interpretation of VF from January 1, 2012, through December 31, 2012. Data were collected regarding the referring department, indication for the VF, interpretation of the VF and comparison with any prior VFs, any associated interventions with the VF, and available follow-up VFs. The main outcome measures included 1) characterizing the use of remote VF interpretations and 2) how many remote VF interpretation results were consistent with the referring diagnosis based on the patient's clinical history and imaging. Results: One hundred eighty patients received remote interpretation of VFs. The most frequent referring departments were endocrinology (79; 44%), neurology (51; 28%), and neurosurgery (43; 24%). The VF indications included parasellar lesion (107; 59%), seizure disorder (26; 14%), meningioma (19; 11%), vascular lesion (11; 6%), and others (17; 9%). There were 78 patients (43%) that had an intervention before the VF, whereas 49 (27%) were preoperative VFs. Eighty-seven (48%) of the VFs were interpreted as abnormal. Of all the 180 remote interpretation of VFs, 156 (87%) had VF interpretations that were consistent with the clinical question posed by the referring provider based on clinical history and imaging. Among the other 24 remote VF interpretations (13% of total remote VF interpretations), there was no clear interpretation because of either additional unexpected VF defects (n = 5, 21%), VF defect mismatch (n = 6, 25%), or unreliable VFs (n = 13, 54%). The median wait time for patients receiving remote VF interpretations was 1 day. Conclusions: Remote interpretation of VFs was most often requested by endocrinology, neurology, and neurosurgery and could be performed very quickly. The most common indications were parasellar lesions, and just less than half of patients receiving remote VF interpretations had a prior intervention. A majority of remote VF interpretations were able to answer the clinical question, given the patient's clinical history and imaging. Remote interpretation of VFs may thus offer referring departments a more efficient method of obtaining VF interpretations than in-office neuro-ophthalmology examinations.